Sistema para perfilagem de fundo na zona de arrebentação utilizando sensor de pressão - DE QUADROS, CLÉCIO JOSÉ LOPES; MARONE, EDUARDO; PRATA JR, VICENTE DE PAULA; DE ARAÚJO, ALFREDO DUARTE (Pesquisas em Geociências, 2001)
On this work, a successful device, fully developed at the Marine Physics Lab of the Center for Marine Studies of the Federal University of Paraná, Brazil is presented. Beside the working principles. the bottom profile methodology, also developed for this particular instrument, is described. Some examples, showing results obtained by the use of such instrumented sleigh are , also depicted here. The system consists in un aluminum base, in a form of a snow sledge, equipped with a mini-STD, which is capable to measure at time rate of up to 1 measure each 1 or 5 seconds, water temperature and salinity. as well as the water column height. The pressure sensor has an accuracy of up to 1 cm. The device is deployed behind the breaking zone using a fisherman or small rubber boat, capable to depart from the beach. The device, measuring at its maximum rate, is then recovered using a long graduated and weighted rope. The recovering is performed, in a straight line, with intervals of 9 meters, stopping for a short period to obtain enough data in fixed points. When the device is still underwater, but near the beach, a leveling rod is located at the pressure sensor in order to reference the vertical profiles to a fixed land benchmark by using a precision topographic level. The topographic leveling is also performed over the beach. Pressure data are then filtered from wave action at lab, resulting in a full and complete topographic profile, from behind the breaking zone up to any reference point at the back of the sandy beach. The sledge format, the weighted rope and the filtering procedures ensured straight line profiling and an adequate elimination of the surface waves signal. The topographic profiles obtained and presented as examples, shown enough accuracy in depicting the effect of meteorological fronts over the sampled beaches.